Preparation and photophysical properties of fluorescent difluoroboronated β-diketones having phenanthrene moieties studied by emission and transient absorption measurements. Issue 2 (26th January 2016) - Mamiya, Michitaka; Suwa, Yurie; Okamoto, Hideki; Yamaji, Minoru
Abstract : Six difluoroboronated β-diketones having the phenanthrene skeleton (Phe@Ar) are prepared, and the photophysical features are studied. Abstract : Six difluoroboronated β-diketones having the phenanthrene skeleton (Phe@Ar) are prepared. Based on the measurements of the fluorescence quantum yields, lifetimes and transient absorption, the photophysical features of Phe@Ar are studied in comparison with those of difluoroboronated diketones having phenyl, naphthyl and anthryl moieties. β-Diketones having 1-, 2-, 3- and 9-phenanthryl moieties (PheDKAr) were prepared as the precursor to Phe@Ar. 1-Acetylphenanthrene was synthesized by the photocyclization method as the key building block of PheDKAr having the 1-phenanthryl moiety. The counter aromatic moieties (Ar) of the prepared PheDKAr are varied with phenyl, furyl and thienyl rings (Ar = Ph, F and T, respectively) to investigate the effects of π-conjugation on the fluorescence properties. The prepared Phe@Ars are fluorescent with appreciable fluorescence quantum yields which depend on the substitution position of the phenanthrene moiety. 3-Phe@Ph having the 3-phenanthryl moiety provides the largest fluorescence quantum yield (0.81) in acetonitrile among the Phe@Ars whereas 2-Phe@Ph having the 2-phenanthryl moiety shows the smallest fluorescence quantum yield (0.07) in acetonitrile. All the Phe@Ars show fluorescence also in the solid state, and the fluorescence spectra and quantum yields were determined. Transient absorption measurement using laser flash photolysis of the Phe@Ars revealed the triplet formation. DFT and TD-DFT calculations of Phe@Ars rationalize the dependency of the fluorescence quantum yields on the substitution position of the phenanthrene skeleton in terms of difference in the oscillator strength for the HOMO–LUMO transition.